Diseño de un sistema de generación de energía eléctrica a partir de fuentes de energías renovables para cubrir las necesidades del internado rural camino verde del municipio de Uribia la Guajira (2023)
This degree work proposed the design of an energy generation system through renewable sources in the camino verde ethno-educational institution in the Municipality of Uribia, department of La Guajira. Said work started from the problems that arise in the educational establishment with the deficiency of electrical fluid and the need for a wind or photovoltaic energy generation system that guarantees the connectivity and operation of the equipment in the computer room and takes a educational process with dignity. To achieve the proposed objectives, a descriptive investigation was carried out. It was determined that the available resources of the irradiation area and average wind speed at 10 meters high are 4.5-5.0 kwh/m², and 4-10 m/s respectively, likewise the approximate energy demand in alternating current in the computer room is 8980 Wh/day. A 3150 photovoltaic system is determined with one day of autonomy, six 12V 300 Ah batteries, seven 450 W solar panels, a 100 A-24 V solar regulator and a 5000 W-24 V inverter with an approximate cost of $30,128,149.00 Colombian pesos. In the same way, a wind system is obtained with a Bornay Wind 25.3 + 5000 W wind turbine, 12 BAE 24 V 1160 Ah stationary batteries of 2 V each, a 10 m tower, an MPPT Wind + 24 vdc regulator and a maximum intensity of 125 Amp. , a 24 Vdc/110 Vca-5000 W pure wave inverter, accessory and additional items with an approximate cost of $115,380,840.00. The benefit is established directly for 421 students who use the computer room.